2022
DOI: 10.1111/2047-3095.12390
|View full text |Cite
|
Sign up to set email alerts
|

Missed nursing care in the COVID‐19 pandemic in Iran

Abstract: Background Quality of care is one of the most critical issues in nursing care today. Moreover, all health care employees are responsible for providing support and high‐quality, safe care. However, nurses caring for COVID‐19 patients face problems such as unfamiliar work environments, exposure to the disease, lack of experience in their new positions, and close public and media attention. This study aimed to investigate missed nursing care and the reasons for missed nursing care during the coronavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
2
14
1
1
Order By: Relevance
“…The nding of this study showed that in addition to the rules and regulations related to the nursing profession, nurses are burdened with long working hours, performing non-specialized tasks, and in exibility in working hours, which, in line with the ndings of another study in Iran (25). Singh and colleagues (2020) reported that the experienced stress by nurses is related to the working environment, which describes the individual's perception and reaction to work-related demands and the ability to adapt to these demands (26).…”
Section: Discussionsupporting
confidence: 87%
“…The nding of this study showed that in addition to the rules and regulations related to the nursing profession, nurses are burdened with long working hours, performing non-specialized tasks, and in exibility in working hours, which, in line with the ndings of another study in Iran (25). Singh and colleagues (2020) reported that the experienced stress by nurses is related to the working environment, which describes the individual's perception and reaction to work-related demands and the ability to adapt to these demands (26).…”
Section: Discussionsupporting
confidence: 87%
“…Study locations ranged from a hospital (e.g., [ 35 ]) to specific hospital settings (tertiary [ 55 ], district [ 51 ], government [ 56 ], private [ 34 ], teaching [ 50 ]) in various types of units (e.g., medical/surgical [ 54 ], urology [ 43 ], cardiology [ 48 ]). In addition, COVID-19 units were included in two studies [ 22 , 37 , 41 ] and nursing homes in another two [ 22 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…All these cross‐sectional studies determined the prevalence of missed nursing care and the possible determinants. Furthermore, 14 studies analyzed the influence of missed nursing care on nurses and organizational outcomes (Alfuqaha et al, 2023; Bartoníčková et al, 2022; Cengia et al, 2022; Edmonds et al, 2022; Falk et al, 2022; Ferreira, 2022; Gurková, Mikšová, & Šáteková, 2021; Hosseini et al, 2022; Khrais et al, 2023; Nymark et al, 2022; Obregón‐Gutiérrez et al, 2022; Özdeli̇Kara & Yaman, 2021; Qureshi et al, 2022; von Vogelsang et al, 2021). Two studies compared missed nursing care during different phases of the COVID‐19 pandemic (Falk et al, 2022; Nymark et al, 2022), and one study compared the perception of nurses about missed nursing care before and during the COVID‐19 pandemic (Alfuqaha et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were conducted between April 2020 and August 2021 in six European countries (n = 13; Bartoníčková et al, 2022;Cengia et al, 2022;Falk et al, 2022;Gurková, Bartoníčková, et al, 2021;Gurková, Mikšová, & Šáteková, 2021;Jørgensen et al, 2021;King et al, 2021;Moretti et al, 2021;Nymark et al, 2022;Obregón-Gutiérrez et al, 2022;Senek et al, 2022;Sugg et al, 2021;von Vogelsang et al, 2021), four Asian countries (n = 8; Alfuqaha et al, 2023;Alsolami, 2021;Hosseini et al, 2022;Khrais et al, 2023;Labrague et al, 2022;Pourmovahed et al, 2022;Safdari et al, 2022Safdari et al, , 2023, two North American countries (n = 2; Edmonds et al, 2022;Qureshi et al, 2022), one South American country (n = 1; Ferreira, 2022), and one transcontinental country (n = 1; Özdeli Kara & Yaman, 2021).…”
Section: Description Of Included Studiesmentioning
confidence: 99%